Perlawanan Masyarakat Samin (Sedulur Sikep) Atas Kebijakan Pembangunan Semen Gresik Di Sukolilo Pati (Studi Kebijakan Berbasis Lingkungan Dan Kearifan Lokal) - Subarkah .; Anggit wicaksono (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
Pluralistic  society  is  a  rich  culture  that  is  always  maintained  and  preserved  in  which  there  are values,  and  norms  prevailing  in  the  society,  therefore  the  increased  pace  of  development,  any development  planning  where  customs  values,  norms,  culture,  who  have  local  knowledge  (local wisdom) need to be taken into account by looking at a holistic approach to the environment. Issues that  arise  in  the  district  Sukolilo  Pati,  the  Samin  community  or  Sedulur  resistance  against  the construction of Semen Gresik Sikep is very interesting to study or do research more deeply both doctrinal and non-doctrinal. This study used a Constructivist paradigm , which views law as the law as relative and contextual consensus  (  law  on  hakektnya  an  agreement  ,  whether  written  mapun  unwritten  are  relative  and contextual ) approach socio legal studies legal problems are not merely conceived as the norm and simultaneously interpret the law as behavior . Local knowledge is a form of appreciation of humanity and as a servant of God in the process of social  interaction  ,  not  only  with  our  fellow  human  beings  ,  but  also  to  the  environment  .  Sikep Sedulur understanding of the environment that have so far not included a simple lifestyle change that has been handed down , including ecological balance is maintained and well preserved with two (2 ) aspects: Aspect and Aspect Emperik transcendental . Samin community of resistance to the  paradigm  associated  with  environmental  and  healthy  good  life  in  accordance  with  local knowledge  .  Language  of  "  welfare  "  is  understood  differently  by  people  because  it  's  simple pattern  has  been  both  physically  and  spiritually  prosperous  so  that  the  construction  of  a  cement plant with mining limestone ( karst ) it will damage the environment and make people suffer Keywords: local wisdom, policy